Understanding Compliance With Paying Zakat: Insights From Recent Literature - Azis, Saipul; Hulwati, Hulwati; Novia, Aidil (Universitas Islam Negeri Alauddin Makassar, 2024)
This study aims to understand zakat compliance through the latest literature review from 2020-2024. The method used is a literature study by collecting and analyzing data from relevant scientific articles. Data analysis uses content analysis to identify and categorize the main themes that emerge from the analyzed literature, as well as thematic analysis to identify recurring patterns or themes in the data. While the analysis tools use the Vosviewr application, Microsoft Excel and Mendeley. The results of the study show that the latest literature insights from 2020-2024 have 15 variables with the most appearances in publications on zakat, including attitudes 78 occurrences, knowledge 63 occurrences, zakat institutions 62 occurrences, income 55 occurrences, compliance behavior 52 occurrences, influence 52 occurrences, religiosity 52 occurrences, income zakat 43 occurrences, subjective norms 43 occurrences, trust 41 occurrences, awareness 34 occurrences, professional zakat 18 occurrences, self-efficacy 18 occurrences, BAZNAS 14 occurrences, and accountability 13 occurrences. By understanding the variables that influence the fulfillment of zakat, it is hoped that the level of fulfillment can increase, so that zakat collection will also increase. This will support the redistribution of wealth and facilitate poverty alleviation efforts.